Active current ripple cancellation in parallel connected buck converter modules. Issue 4 (1st April 2013) - Tsang, Chi‐Wa; Foster, Martin; Stone, David; Gladwin, Dan
Abstract : Parallel connection of converters has become a popular method of improving efficiency. This study first presents a design technique for a buck converter with two parallelly connected power modules (PMs), where one PM is designed with large current ripple for high efficiency. This study then demonstrates an active current ripple cancellation technique, where the current waveform of the second PM is shaped to be the exact opposite to that in the first PM, to reduce the current ripple as seen by the output capacitor. The factors that affect the overall efficiency in a parallel connected converter and the calculation of the parameters that determine the effectiveness of the ripple cancellation are reported. A prototype parallel converter is designed based on the proposed converter design technique and the current ripple seen by the output capacitor is successfully reduced by 66% with the proposed ripple cancellation technique, under different line and load conditions.